2006
DOI: 10.1016/j.exphem.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Design of homogeneous, monopegylated erythropoietin analogs with preserved in vitro bioactivity

Abstract: Objective-Erythropoietin (Epo) bioactivity is significantly reduced by modification of lysine residues with amine-reactive reagents, which are the most commonly used reagents for attaching polyethylene glycols (PEGs) to proteins to improve protein half-life in vivo. The aims of this study were to determine whether Epo bioactivity can be preserved by targeting attachment of maleimidePEGs to engineered cysteine analogs of Epo, and to determine whether the PEGylated Epo cysteine analogs have improved pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
(39 reference statements)
1
29
0
2
Order By: Relevance
“…Our data reveal that neighbor residue Thr27 is more suitable than Thr26 because cysteine substitution at this position does not affect N-glycosylation at position 24. As indicated in Table 3, the E89C analog has good criteria for cysteine PEGylation, high SAA and low RMSD, which is consistent with the previous study by Long et al 2 Even being PEGylated with a highmolecular-weight (20 kDa) PEG-maleimide, the E89C analog shows the same activity.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Our data reveal that neighbor residue Thr27 is more suitable than Thr26 because cysteine substitution at this position does not affect N-glycosylation at position 24. As indicated in Table 3, the E89C analog has good criteria for cysteine PEGylation, high SAA and low RMSD, which is consistent with the previous study by Long et al 2 Even being PEGylated with a highmolecular-weight (20 kDa) PEG-maleimide, the E89C analog shows the same activity.…”
supporting
confidence: 79%
“…32 PEGylation of positions located in the N-terminal (R4 and L5) and C-terminal (R162, T163, and R166) in the EPO are not logical because of spatial restriction in interaction between EPO and its receptors. As shown by Long et al, 2 the attachment of 20 kDa PEG at positions A1, P3, and T163 decreases receptor binding affinity. In addition, it has been reported that terminal arginine of EPO is deleted from the CHO-expressed rhEPO.…”
mentioning
confidence: 92%
See 3 more Smart Citations